Language and Culture of Young Arabs in Banjarmasin - Taufiqurrahman, Taufiqurrahman; Almajudha, Yahana; Noor, Fatwiah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This study aimed to know the use of Arabic language and the application of Arabic culture by young people of Arab descent in Banjarmasin City in their daily lives. The methodology used is qualitative research with an ethnographic approach. Data collection was done through observation, interviews, and documentation. Interviews were conducted with young people of Arab descent who live in Banjarmasin City. The results showed that the beginning of the arrival of Arabs to Banjarmasin City was related to their journey from Surabaya, then sailed by sea to Nagara, continued to Kuin in Banjarmasin City and then formed a settlement from their community which was later called an Arab village. The language and culture of the Arab descendants of Banjarmasin city are diverse, with code-mixing and code-switching, wedding traditions, religious events, food, and more. But, not all of them use the language and practice typical Arabic culture very strongly. Their language, culture and daily activities often follow those of general Banjarmasin people.